Notes on a Collection of Polishers and other Objects found on the Site of the Roman Fort at Newstead, Melrose - Corrie, John (Proceedings of the Society of Antiquaries of Scotland, 1914)
On the basis of the fact that only two burials were encountered during excavation it is argued that a cemetery must exist on the outskirts of the fort. With this in mind a systematic search recovered a collection of objects which included twenty three burnishers or polishers, fourteen gaming pieces, ten fragments of beads, a portion of a glass armlet and a brooch.